1982
DOI: 10.1128/aem.44.1.12-18.1982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental conditions during heating on commercial spore strip performance

Abstract: Commercial biological indicator spore strips in glassine envelopes, produced by three manufacturers, were evaluated by fraction-negative procedures after being heated at 121.0 ± 0.05°C. Only one type of spore strip met the manufacturer's specifications. The strips of one manufacturer were further evaluated by fractionnegative and survivor curve-plate count procedures after being heated under several conditions (enclosed in glassine envelopes, in trypticase soy broth plus 0.0015% bromocresol purple, in Tryptica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…globigii, sonication in 70% ethanol may be effectively used to compare concentrations of spores on strips with those of the initial inoculum. Recovery rates in excess of 100% have been substantiated by earlier studies (Brown and Gaze 1988;Smith et al 1982) in which, for certain conditions, recovery was greater than the expected initial inoculum. Sonication treatment provided better recovery than did vortex treatment regardless of the suspension medium (Butterfield's buffer, 70% ethanol or 0.1% Tween 80) for B. stearothermophilus spore recovery (Table 1).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…globigii, sonication in 70% ethanol may be effectively used to compare concentrations of spores on strips with those of the initial inoculum. Recovery rates in excess of 100% have been substantiated by earlier studies (Brown and Gaze 1988;Smith et al 1982) in which, for certain conditions, recovery was greater than the expected initial inoculum. Sonication treatment provided better recovery than did vortex treatment regardless of the suspension medium (Butterfield's buffer, 70% ethanol or 0.1% Tween 80) for B. stearothermophilus spore recovery (Table 1).…”
Section: Discussionmentioning
confidence: 79%
“…Brown and Gaze (1988) reported recovery close to the manufacturer's claim of 1 x lo5 viable spores strip-' from unheated, paper spore strips (from 4.4 x 10' to 1.3 x lo5 spores strip-' were recovered using glass beads and a wrist action shaker). Smith et al (1982) determined the initial number of spores per commercial paper strip using both the Waring blender and the mortar and pestle methods. For one type of commercial spore strip, recovery was more than a log greater than the manufacturer's specification.…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for this discrepancy is that D-values for SBI lots are calcu-lated from spore survivor curves (obtainable from the producer on request), while D-values for ABI lots (given in their label claims) are based on results from fraction-negative tests. There can be considerable difference between D-values determined in parallel by the two methods, those based on fraction-negative testing being the lowest (7). It is important that comparative thermoresistance characteristics of different BIs should be based on tests performed under approximately equal test conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The thermoresistance characteristics of BIs depend on many factors, among which are package configuration and heating conditions (3,7). Consequently, extrapolation of the data referred to above (5,6), i.e.…”
mentioning
confidence: 99%
“…These higher D-values might be caused by the longer heat-up time required due to the presence of moisture or liquid. Smith et al (1982) attempted to correct for this delay and obtained similar D-values for both strips enclosed in glassine envelopes (2.81 min) and those unenclosed in envelopes and submerged in water-for-injection (2.74 min). In this same study it was found that D-values for dry strips unenclosed in glassine envelopes were higher than those of dry strips enclosed in glassine envelopes (4.95 vs. 2.81 min).…”
Section: Evaluation Of Causes Of Spore Strip Failurementioning
confidence: 99%